Addressing Childhood Obesity in Georgia: Past, Present, and Future - Debra Kibbe; Emily Vall; Christine Green; Brenda Fitzgerald; Karen Minyard; Kelly Cornett (Georgia Southern University, 2016)
Background: The Trust for America's Health ranks Georgia 17th (16.5%) in the nation for childhood obesity prevalence among youth aged 10-17 years. Georgia has a long history of addressing childhood obesity at the state, regional, and local levels. This report outlines the historical efforts in childhood obesity in Georgia from the mid-1990's to the present, summarizes current childhood obesity prevention and management strategies, and provides childhood obesity-related data relevant to the current strategies. Methods: Childhood obesity-related efforts in Georgia from 1996 to the present are documented, along with how these efforts led to the creation of Georgia Shape. The Georgia Shape Childhood Obesity Prevention Initiative, created by Governor Nathan Deal in 2012, established a statewide, 10-year plan of action to address childhood obesity. It convenes more than 125 governmental, philanthropic, academic and business community partners quarterly to work towards reducing the incidence of childhood obesity and overweight in Georgia. Evidence supporting the Georgia Shape objectives is described, along with current program and policy efforts that may allow achievement of its goal of having 69% of Georgia's children in a healthy weight range by the year 2023. Results: Georgia's obesity rate for low-income, 2- to 4-year old children has decreased. Over the 2013-2015 school years, there has been no increase in BMI at the population level among school age children and youth, and the percentage of boys and girls with increased aerobic capacity has improved. Future efforts should focus on middle and high school students; engaging and educating parents of young children; and state policies that support safe, daily physical activity and access to healthy, local food. Conclusions: A long history of childhood obesity activities in Georgia has led to a strategic plan of action, with contributions from many stakeholders. These efforts aim to reduce the prevalence of childhood overweight and obesity in Georgia over 10 years.